Humoral Responses to Rv1733c, Rv0081, Rv1735c, and Rv1737c DosR Regulon-Encoded Proteins of Mycobacterium tuberculosis in Individuals with Latent Tuberculosis Infection. (1st February 2017) - Kimuda, Simon G.; Nalwoga, Angela; Levin, Jonathan; Franken, Kees L. M. C.; Ottenhoff, Tom H. M.; Elliott, Alison M.; Cose, Stephen; Andia-Biraro, Irene
Abstract : Latent tuberculosis infection (LTBI) is evidence of immunological control of tuberculosis. Dormancy survival regulator (DosR) regulon-encoded proteins may have a role in the maintenance of LTBI. T cell responses to Rv1733c, Rv0081, Rv1735c, and Rv1737c DosR regulon-encoded proteins were found to be most frequent among household contacts of TB cases from Uganda compared to other DosR proteins, but antibody responses were not described. We characterized antibody responses to these proteins in individuals from Uganda. Antibodies to Rv1733c, Rv0081, Rv1735c, and Rv1737c DosR regulon-encoded proteins were measured in 68 uninfected individuals, 62 with LTBI, and 107 with active pulmonary tuberculosis (APTB) cases. There were no differences in the concentrations of antibodies to Rv0081, Rv1735c, and Rv1737c DosR regulon-encoded proteins between individuals with LTBI and APTB and those who were uninfected. LTBI was associated with higher concentrations of antibodies to Rv1733c in female participants [adjusted geometric mean ratio: 1.812, 95% confidence interval (CI): 1.105 2.973, and p = 0.019 ] but not in males (p value for interaction = 0.060). Antibodies to the four DosR regulon-encoded proteins investigated may not serve as good biomarkers of LTBI in the general population. More of the M.tb proteome needs to be screened to identify proteins that induce strong antibody responses in LTBI.